Pengaruh Peran Orang Tua terhadap Motivasi Belajar Siswa Kelas V Madrasah Ibtidaiyah Swasta Al-Zaytun Sekolah Kita Indramayu - Nurul Hidayat; Abdur Rahim; Ahmad Asrof Fitri (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
This research examines the influence of the role of parents on the learning motivation of fifth grade students at Al-Zaytun Private Madrasah Al-Zaytun School, Kita Indramayu. The family has a very important role in educational activities. So this is where the role of parents is needed to create a conducive environment so as to increase the potential, intelligence, and self-confidence of children. The purpose of this research is to find out how the influence of the role of parents on students' learning motivation. This type of research is quantitative research. This research was conducted in Class V Madrasah Ibtidaiyah Al-Zaytun Private School, Kita Indramayu, with a total of 16 students consisting of 11 boys and 5 girls as subjects. This research method uses a quantitative approach with prerequisite analysis test techniques and hypothesis proof techniques. The hypothesis testing technique that the authors took in this study was a simple linear regression analysis technique aimed at knowing the form of the relationship (influence) between variable x (role of parents) to variable y (learning motivation). The author uses the SPSS version 22 program in proving the hypothesis. The final analysis in this study is a simple linear regression test. The simple linear regression test value obtained is a significant value of 0.136 > 0.05, so it can be concluded that the parental role variable (X) has no effect on the learning motivation variable (Y) and the t value is 1.583 <t table 2.145, so it can be concluded that the Parental Role variable (X) has no effect on the Learning Motivation variable (Y). Then H0 is accepted and H1 is rejected. Thus, the results of the final analysis in this study read "There is no influence of the role of parents on the learning motivation of fifth grade students of MIS Al-Zaytun Sekolah Kita Indramayu".